Influence of fertilizer on coumarin content and biomass production in Mikania glomerata sprengel - Pereira, Ana Maria Soares [UNESP]; Menezes, A.; Câmara, Francisco Luiz Araújo [UNESP]; Franca, S. C. (My University, 1998)
Mikania glomerata Sprengel leaf extracts have been used in cough syrup formulations due to the presence of active coumarin derivatives. Yields of such natural compounds in cultivated plants can be affected by several nutritional factors. To determine the effect of fertilization on biomass productivity, organ proportion and coumarin content, Mikania glomerata plants were submitted during one year to treatments with organic (humus or manure) and inorganic (different levels of nitrogen) fertilizers. Coumarin concentration was raised by organic fertilization, inorganic nutrients induced increased phytomass (stem and leaf) yield, however no fertilized plants showed enhanced leaf production.
Keywords: Expectorant; Folk medicine; Guaco; Medicinal plant; coumarin derivative; expectorant agent; fertilizer; plant extract; biomass; crop plant; fertilizer application; yield response; Brazil; coughing; fertilization; medicinal plant; nonhuman; phytochemistry; plant growth; traditional medicine; Mikania; Mikania congesta; Mikania glomerata